2018
DOI: 10.1507/endocrj.ej17-0542
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of 5α-reductase type 2 deficiency due to mutations (p.Q6X, p.R246Q) in <i>SRD5A2</i> gene

Abstract: Abstract. Early diagnosis and optimal management for steroid 5α-reductase type 2 deficiency (5α-RD2) patients are major challenges for clinicians and mutation analysis for the 5α-reductase type 2 (SRD5A2) gene is the golden standard for the diagnosis of the disease. In silico analysis of this enzyme has not been reported due to the lack of appropriate model. Moreover, the histological and pathological changes of the gonads are largely unknown. In the present study, a 5α-RD2 patient born with abnormal external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Functional enrichment analysis revealed significant entries for the androgen biosynthesis processes and follicle stimulating hormone responses, including SRD5A2, SRD5A3, and PAWR genes. Among them, mutations of the SRD5A2, which were closely related to testicular decline, could affect the formation of the urethra and external genitalia, leading to hypoplasia of the male reproductive organs [35]. Therefore, polymorphisms of the SRD5A2 gene may be a key point leading to intersexuality in sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional enrichment analysis revealed significant entries for the androgen biosynthesis processes and follicle stimulating hormone responses, including SRD5A2, SRD5A3, and PAWR genes. Among them, mutations of the SRD5A2, which were closely related to testicular decline, could affect the formation of the urethra and external genitalia, leading to hypoplasia of the male reproductive organs [35]. Therefore, polymorphisms of the SRD5A2 gene may be a key point leading to intersexuality in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Functional enrichment of the sequencing data for intersex sheep and normal sheep populations (including Tan sheep) did not find significant entries related to gonadal development or sex hormone metabolisms. A previous study reported that testicular tissue dysplasia was a key cause of human gender developmental disorders [35]. Additionally, the excessive synthesis of estrogen in vivo also affected the formation and development of female reproductive organs.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional (3D) structure of the human IR (PDB ID: 2HR7) was downloaded from RCSB Protein Data Bank ( http://www.rcsb.org/pdb/home/home.do ) [ 21 ]. The 2D structures of the galangin and pinocembrin were drawn by ChemBioDraw Ultra 14.0 and converted to 3D structures by the ChemBio3D Ultra 14.0 package [ 22 ]. The AutoDockTools 1.5.6 package [ 23 , 24 ] was employed to generate the docking input files.…”
Section: Methodsmentioning
confidence: 99%
“…For Vina docking, the default parameters were used if it was not mentioned. The best-scoring pose as judged was chosen by the Vina docking score and visually analyzed using PyMoL 1.7.6 software ( http://www.pymol.org/ ) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, the testes of the affected 46,XY individuals are expected to differentiate normally and indeed, several reports have revealed intact histology of the testes in 5αRD patients during infantile and toddler periods ( 13 , 14 ); however, almost all patients suffer from azoospermia or oligospermia during adulthood, indicating that deterioration of spermatogenesis likely occurs after infantile and toddler periods ( 13 , 14 , 15 , 16 ). Although there is evidence to show that the lack of 5 alpha-reductase type 2 activity itself affects germ cell numbers in 5αRD patients ( 14 , 16 ), accompanying cryptorchidism has also been observed to adversely affect spermatogenesis, suggesting that the underlying mechanisms of defective spermatogenesis are complex.…”
Section: Introductionmentioning
confidence: 99%